2019
DOI: 10.1016/j.biopsycho.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A potential mechanistic role for neuroinflammation in reward processing impairments in autism spectrum disorder

Abstract: Accumulating evidence suggests that autism spectrum disorder (ASD) may be conceptualized within a framework of reward processing impairments. The "Social Motivation Theory of Autism" posits that reduced motivation to interact with people and decreased pleasure derived from social interactions may derail typical social development and contribute to the emergence of core social communication deficits in ASD. Neuroinflammation may disrupt the development of mesolimbic dopaminergic systems that are critical for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 213 publications
(247 reference statements)
1
10
0
Order By: Relevance
“…Nevertheless, the observations regarding the general dysfunction of the reward circuitry in individuals with ASD [13], along with the positive results of OXT administration in murine models [28,29], prompted the use of OXT as a therapeutic means in individuals with ASD. While some trials showed a promising beneficial effect of OXT on social behavior via modulation of the reward pathway [33][34][35], several meta-analyses failed to demonstrate a clear-cut benefit of OXT over placebo in alleviating autistic core symptoms [36][37][38].…”
Section: Oxytocinmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the observations regarding the general dysfunction of the reward circuitry in individuals with ASD [13], along with the positive results of OXT administration in murine models [28,29], prompted the use of OXT as a therapeutic means in individuals with ASD. While some trials showed a promising beneficial effect of OXT on social behavior via modulation of the reward pathway [33][34][35], several meta-analyses failed to demonstrate a clear-cut benefit of OXT over placebo in alleviating autistic core symptoms [36][37][38].…”
Section: Oxytocinmentioning
confidence: 99%
“…The need for novel therapeutics remains acute as knowledge of new molecular targets has yet to be translated into clinical practice [62]. However, as new insights into the dopamine signaling anomalies in ASD stem from animal models [70][71][72][73][74][75], as well as neuroimmune theoretical frameworks [13,76,77], novel treatment approaches emerge.…”
Section: Dopamine Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on putative causal aspects that conduct to the different manifestations of ASD remains a priority. The role of dopaminergic neurotransmission and its involvement in the causal pathway of ASD deserves attention in this regard (Ayano, 2016;Greene, Walsh, Mosner, & Dichter, 2018;Pavăl, 2017). For example, disruptions in the nigrostriatal pathway, classically linked to motor functions, has been proposed as a potential contributing cause of some motor repetitive behaviours in ASD whereas disturbances in the mesocorticolimbic pathway, involved in reward and cognitive related functions, may lead to social cognitive an affective impairments, (FernĂĄndez, Mollinedo-Gajate, & Peñagarikano, 2018;Supekar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing emphasis on the contribution of factors outside the brain in regulating central processes. Indeed, a growing body of research focuses on the ability of both the endocrine and the immune system on modulating reward processes (Adam & Epel, 2007;Anisman et al, 1996;Goeders, 2002;Greene et al, 2019;Montesinos et al, 2016;Ye et al, 2001). Over the past decade a new player has emerged as another key factor in sculpting reward circuits across the lifespan, namely, the gut microbiome, which encompasses the trillions of bacteria in our gut.…”
mentioning
confidence: 99%